Waste Foundry Sand as Permeable and Low Permeable Barrier for Restriction of the Propagation of Lead and Nickel Ions in Groundwater. (31st July 2020) - Faisal, Ayad A. H.; Al-Ridah, Zaid Abed; Naji, Laith A.; Naushad, Mu.; El-Serehy, Hamed A.
Abstract : This work aims to investigate the ability of using waste foundry sand (WFS) resulting as inexpensive by-product from steel industry in the low permeability barrier (LPB) and permeable reactive barrier (PRB) technologies for restriction of the movement of lead and nickel ions in the groundwater. Outputs of flask and tank tests certified that this material could capture these ions with sorption efficiency greater than 95% at time, pH, sorbent dosage, and speed equal to 60 min, 4 for lead and 6 for nickel, 2.5 g/100 mL, and 250 rpm, respectively. Sorption isotherm measurements were represented in a good manner by Langmuir model in comparison with Freundlich model with coefficient of determination ( R 2 ) greater than 0.99. So, the chemisorption was the predominant mechanism which could be supported by O-H, H-O-H, C-O, O-Si-O, and Si-O functional groups based on the Fourier transform infrared analysis. The maximum sorption capacity of WFS was 13.966 and 4.227 mg/g for lead and nickel ions, respectively, with corresponding affinities equal to 0.647 and 0.099 L/mg. Measurements signified that the hydraulic conductivity of WFS was 3.8 × 10 −7  cm/s which satisfies the requirements of LPB. To obtain the acceptable values of permeability and reactivity, PRB was prepared from mixing 18% WFS with 82% filter sand. COMSOL software was able to simulate the measurements of two-dimensional tank packed with Iraqi soil aquifer in combination with WFS-LPB and WFS-filter sand PRB. Thicker barriers have a high ability in the protection of locations in the down-gradient side because their longevity increased dramatically with increase of barrier thickness.